High resolution interface circuit for closed-loop accelerometer - 尹亮 刘晓为 陈伟平 周治平 (Journal of semiconductors, 2011)
This paper reports a low noise switched-capacitor CMOS interface circuit for the closed-loop operation of a capacitive accelerometer.The time division multiplexing of the same electrode is adopted to avoid the strong feedthrough between capacitance sensing and electrostatic force feedback.A PID controller is designed to ensure the stability and dynamic response of a high Q closed-loop accelerometer with a vacuum package.The architecture only requires single ended operational amplifiers,transmission gates and capacitors.Test results show that a full scale acceleration of±3 g,non-linearity of 0.05%and signal bandwidth of 1000 Hz are achieved.The complete module operates from a±5 V supply and has a measured sensitivity of 1.2 V/g with a noise of floor of 0.8μg/（Hz）1/2 in closed-loop.The chip is fabricated in the 2μm two-metal and two-poly n-well CMOS process with an area of 15.2 mm2.These results prove that this circuit is suitable for high performance micro-accelerometer applications like seismic detection and oil exploration.